Circulating levels of mitochondrial oxidative stress-related peptides MOTS-c and Romo1 in stable COPD: A cross-sectional study - Amado, Carlos A.; Martín-Audera, Paula; Agüero, Juan; Lavín, Bernardo A.; Guerra, Armando R.; Boucle, Daymara; Ferrer-Pargada, Diego; Berja, Ana; Martín, Fernando; Casanova, Ciro; García-Unzueta, Mayte (Frontiers in Medicine, 2023)
Background MOTS-c and Romo1 are mitochondrial peptides that are modulated by oxidative stress. No previous studies have explored circulating levels of MOTS-c in patients with chronic obstructive pulmonary disease (COPD). Methods We enrolled 142 patients with stable COPD and 47 smokers with normal lung function in an observational cross-sectional study. We assessed serum levels of both MOTS-c and Romo1 and associated these findings with clinical characteristics of COPD. Results Compared with smokers with normal lung function, patients with COPD had lower levels of MOTS-c (p = 0.02) and higher levels of Romo1 (p = 0.01). A multivariate logistic regression analysis revealed that above-median MOTS-c levels were positively associated with Romo1 levels (OR 1.075, 95% CI 1.005–1.150, p = 0.036), but no association was found with other COPD characteristics. Below-median levels of circulating MOTS-c were associated with oxygen desaturation (OR 3.25 95% CI 1.456–8.522, p = 0.005) and walking <350 meters (OR 3.246 95% CI 1.229–8.577, p = 0.018) in six-minute walk test. Above-median levels of Romo1 were positively associated with current smoking (OR 2.756, 95% CI 1.133–6.704, p = 0.025) and negatively associated with baseline oxygen saturation (OR 0.776 95% CI 0.641–0.939, p = 0.009). Conclusions Reduced levels of circulating MOTS-c and increased levels of Romo1 were detected in patients diagnosed with COPD. Low levels of MOTS-c were associated with oxygen desaturation and poorer exercise capacity using 6 min walk test. Romo1 was associated with current smoking and baseline oxygen saturation. Trial registration www.clinicaltrials.gov; No.: NCT04449419; URL: www.clinicaltrials.gov. Date of registration: June 26, 2020.